غرامات التأخير كجزاء في العقد الإداري - محمد انصاف (Latakia University Journal - Economic and Legal Sciences Series, 2018)
يرتبط مصطلح غرامات التأخير كجزاء مالي بالعقد الإداري، حيث أن لغرامات التأخير وقع خاص على المُتعاقد مع الإدارة تدفعه إلى تنفيذ التزاماته بشكل دقيق، كما أنّها تخضع لنظام قانوني خاص بها مختلف عما هو عليه الأمر في العقود المدنيّة، فهي تُوقع بقرار يصدر عن الإدارة دون اللجوء إلى القضاء، ودون حاجة لإثبات الضرر، لأن التأخُر في تنفيذ العقد الإداري يُعتبر بحد ذاته ضرر يلحق بالمرفق العام الذي رصد العقد لمصلحته، وبالتالي إلحاق الضرر بالمصلحة العامة التي هي الغاية المقدسة من العقد الإداري. The penalty for delay penalties is a financial penalty for the administrative contract. However, the delay fine has a special effect on the contractor with the administration. It is subject to a different legal system that is different from what it is It is in civil contracts It signaled a decision issued by the administration without resorting to the judiciary, and without the need to prove the damage, because the delay in the implementation of the administrative contract is in itself an injury to the public facility that monitors the contract for his benefit and thus harm the public interest which is the holy purpose of the administrative contract.